Literature Review: Analysis Of Participatory Leadership Style - Irham S Damopolii; Andi Indriani Ibrahim; Syahbudin Adam; Abd. Hamid; Rifki Maku; MIftahul Jannah D Lo’o (Universitas Muhammadiyah Palu, 2025)
Leadership plays a crucial role in the success of organizations, both in the education and business sectors. Amidst the dynamics of the modern work environment, the participatory leadership style, which emphasizes the involvement of team members in decision-making, is increasingly gaining attention. This approach is believed to enhance various aspects of organizational performance, ranging from teacher professionalism to employee performance in general. This style involves subordinates in the decision-making, planning, and evaluation processes, thereby creating a more collaborative and inclusive work environment. This literature review aims to analyze and synthesize findings from 20 scientific articles regarding the influence of participatory leadership style on employee performance, professionalism (especially teachers), work motivation, as well as other factors such as communication, work culture, work stress, and service quality in the context of educational organizations (schools, madrasahs, Islamic boarding schools, universities) and other organizations (business, government, hospitals, libraries). This research uses a literature review method with a descriptive-qualitative approach. Analysis was conducted on 20 relevant scientific articles, discussing the implementation and impact of participatory leadership style. Data from each article were extracted based on objectives, methods, context, variables, and main findings related to the influence of participatory leadership, then synthesized to identify patterns, consistency, and differences in results. Literature analysis shows that the participatory leadership style consistently contributes positively to various organizational outcomes. Specifically, it was found that participatory leadership has a positive and significant influence on: Employee/staff performance, Teacher professionalism, Work motivation of employees/teachers. Work motivation was also found to be an important mediator and strongly influenced by communication, Job satisfaction, Organizational commitment, although some studies show insignificant influence, Quality of public services (through employee performance). The participatory leadership style is characterized by subordinate involvement in decision-making, active two-way communication , cooperation , and delegation of authority. Other factors such as work culture , work environment , compensation , and talent management also interact and influence the results. However, some studies also found that participatory leadership style does not always have a significant effect on performance in certain contexts or on work stress. Based on the literature review of 20 articles, it can be concluded that the participatory leadership style generally has a positive and significant influence on improving employee performance, teacher professionalism, work motivation, and job satisfaction in various types of organizations, including educational institutions. Active involvement, open communication, and collaboration are key to the effectiveness of this leadership style. Nevertheless, its success is influenced by the organizational context, work culture, and the readiness of leaders and team members. Challenges such as time and resource limitations need to be managed for the optimal implementation of participatory leadership.